Haiti's Army, Stabilization and Security Sector Governance. Issue 1 (30th September 2016) - Burt, Geoff
Haiti's long and difficult security sector reform (SSR) process has entered a new phase. The reinstatement of the Haitian armed forces, nearly 20 years after former President Jean-Bertrand Aristide disbanded them, adds a new set of actors and more complexity to a process already struggling to deliver results amidst a seemingly endless series of political crises. The armed forces must be an impartial and apolitical institution if they are to contribute to stability in Haiti – an uncertain proposition given their past inability to stay out of the political arena. Building on a summary of the latest developments in the reinstatement process, this paper discusses its implications for Haiti's prolonged international engagement. In particular, the paper focuses on the process to develop a new White Paper on Defence and National Security in Haiti. This process has the potential to contribute to two of the most significant shortcomings of SSR in Haiti, a limited focus on security sector governance and a lack of local ownership. The reinstatement process has been an interesting test case of the international donor community's commitment to the concept of local ownership, long held to be a moral and practical pillar of international engagement. Though reinstatement has been driven by Haitian authorities, the process has struggled to make progress without donor support, raising questions about the appropriate role of international actors in strategic decision-making at the national level. Regardless of their initial reaction to reinstatement, Haiti's international donors risk missing an opportunity to influence the development of an important pillar of Haiti's post-MINUSTAH security sector by choosing to remain on the sidelines.